A murine model of peanut-allergic asthma - Paolucci, Marta; Antz, Nathalie; Homère, Valentine; Kolm, Isabel; Kündig, Thomas M.; Johansen, Pål (Frontiers in Allergy, 2024)
Objectives: Peanut allergy is an IgE-mediated food allergy and associated with asthma in certain patients. With increasing prevalence, its great impact on the quality of life, and a lack of treatment options, the need for new therapy options is given. Hence, models for research and development are required. This study aimed to establish a murine model of allergic airway inflammation induced by peanut allergens.: C3H mice were sensitised by intraperitoneal injections of peanut allergen extract and challenged by an intranasal application of the same extract. Assessment of airway inflammation involved the analysis of immune cells in the bronchoalveolar lavage fluid as measured by flow cytometry. Inflammatory reactions in the lungs tissue were also studies by histology and quantitative PCR. Moreover, peanut-specific immune responses were studied after restimulation of spleen cells in vitro. Results: Sensitisation led to allergen-specific IgE, IgA and IgG1 seroconversion. Subsequent nasal exposure led to allergic airway inflammation as manifested by structural changes such as bronchial smooth muscle hypertrophy, mucus cell hyperplasia, infiltration of eosinophil cells and T cells as well as an upregulation of genes expressing IL-4, IL-5, IL-13 and IFN-. Upon restimulation of splenocytes with peanut allergen, increased secretion of both T-helper type 2 (Th2) and Th1 cytokines was observed.We successfully established a peanut-associated asthma model that exhibited many features characteristic of airway inflammation in human patients with allergic asthma.The model holds potential as a tool for investigating novel therapeutic approaches aimed at preventing the development of allergic asthma.